2018
DOI: 10.1111/cas.13559
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of K‐Ras signaling networks and increased efficacy of epidermal growth factor receptor inhibitors by a novel synthetic miR‐143

Abstract: Despite considerable research on K‐Ras inhibitors, none had been established until now. We synthesized nuclease‐resistant synthetic miR‐143 (miR‐143#12), which strongly silenced K‐Ras, its effector signal molecules AKT and ERK, and the K‐Ras activator Sos1. We examined the anti‐proliferative effect of miR‐143#12 and the mechanism in human colon cancer DLD‐1 cell (G13D) and other cell types harboring K‐Ras mutations. Cell growth was markedly suppressed in a concentration‐dependent manner by miR‐143#12 (IC50: 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 40 publications
5
59
0
Order By: Relevance
“…Furthermore, we demonstrated previously that syn‐miR‐143 functions as a tumor suppressor in BC cells . In an earlier study, we also showed that miR‐143 directly targets KRAS signaling networks . Furthermore, it was reported that miR‐143 also directly targets MSI2 in cervical cancer .…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Furthermore, we demonstrated previously that syn‐miR‐143 functions as a tumor suppressor in BC cells . In an earlier study, we also showed that miR‐143 directly targets KRAS signaling networks . Furthermore, it was reported that miR‐143 also directly targets MSI2 in cervical cancer .…”
Section: Discussionmentioning
confidence: 63%
“…Previously, we have clarified the signaling networks. The “positive circuit” through the constitutive KRAS activation‐stimulation of effector signaling pathways (PI3K/AKT and MAPK) occurs in colorectal cancer, resulting in enhanced nuclear KRAS transcription . As shown in Figure , this cascade was also seen in BC cell lines and, again, the “positive circuit” also occurred in HRAS signaling networks.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations